MENINGKATKAN HASIL BELAJAR MENGGUNAKAN METODE TIPE INDEX CARD MATCH PADA PELAJARAN MATEMATIKA - Puput Wahyu Hidayat; Rina Siti Sari (LP3M STKIP Muhammadiyah Muara Bungo, 2018)
This research is motivated by the low student learning outcomes, the use of improper learning methods, and the index card match learning has never been done at SD Negeri No. 166/II Tirta Mulya. This study aims to improve the process and results of mathematics learning in fifth grade students of SD Negeri No. 166 / II Tirta Mulya Village, by applying the active learning index index match type. This type of research is classroom action research (PTK) which consists of four stages, namely planning, action, observing and reflecting carried out collaboratively. The research was conducted at SD Negeri No. 166 / II Tirta Mulya Village. The subjects of this study were 21 class V students. The study was conducted for 2 cycles. Each cycle consists of 2 meetings. Data collection techniques use test methods, observation sheets and documentation. The data analysis technique is descriptive qualitative and quantitative. The results of the study showed that the index card match type active learning strategy and paying attention to the learning steps to improve the learning process and student learning outcomes, there was an increase in the learning process and student learning outcomes.